2021
DOI: 10.1002/cplu.202100232
|View full text |Cite
|
Sign up to set email alerts
|

New‐Generation Ligand Design for the Gold‐Catalyzed Asymmetric Activation of Alkynes

Abstract: Gold(I) catalysts are ideal for the activation of alkynes under very mild conditions. However, unlike allenes or alkenes, the triple bond of alkynes cannot be prochiral. In addition, the linear coordination displayed by gold(I) complexes places the chiral ligand far away from the substrate resulting in an inefficient transfer of chiral information. This poses a significant challenge for the achievement of high enantiocontrol in gold(I)‐catalyzed reactions of alkynes. Although considerable progress on enantiose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 217 publications
0
18
0
Order By: Relevance
“…We have previously demonstrated that BINOL s and 2,2′-biphenols can be well-chelated with chiral oxazoline-based C^N-cyclometalated gold( iii ) dichloride [(C^N)AuCl 2 , C^N = 2-aryl oxazolinyl] to form C , O - and O , O ′-Au III chelated stable chiral gold( iii ) complexes, respectively. 11 Hence, we reasoned that (±)- DHTP might react with an enantiopure oxazoline-based C^N-cyclometalated gold( iii ) dichloride, resulting probably in two separable diastereomers as access to optically pure ( S )- DHTP and ( R )- DHTP , respectively. Our investigation commenced with the reaction between (±)- DHTP and enantiopure oxazoline-based cyclometalated gold( iii ) dichloride ( R )- 3 .…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that BINOL s and 2,2′-biphenols can be well-chelated with chiral oxazoline-based C^N-cyclometalated gold( iii ) dichloride [(C^N)AuCl 2 , C^N = 2-aryl oxazolinyl] to form C , O - and O , O ′-Au III chelated stable chiral gold( iii ) complexes, respectively. 11 Hence, we reasoned that (±)- DHTP might react with an enantiopure oxazoline-based C^N-cyclometalated gold( iii ) dichloride, resulting probably in two separable diastereomers as access to optically pure ( S )- DHTP and ( R )- DHTP , respectively. Our investigation commenced with the reaction between (±)- DHTP and enantiopure oxazoline-based cyclometalated gold( iii ) dichloride ( R )- 3 .…”
Section: Resultsmentioning
confidence: 99%
“…[100][101][102][103][104][105][106] Therefore, number of other strategies has been introduced to induce enantioselectivity in gold-catalyzed transformations. [107][108][109][110][111][112] As far as CÀ H functionalization is concerned, following approaches have been utilized thus far: 1) use of chiral bulky ligands to create an effective chiral pocket; 2) use of a bifunctional ligand Chemistry-A European Journal capable of establishing secondary interaction with substrates; 3) use of chiral counter-anions; 4) use of chiral organo-catalyst along with achiral gold complex. This article is intended to provide a comprehensive overview of all such transformations under gold catalysis that produce chiral products from achiral substrates.…”
Section: Gold-catalyzed Enantioselective Cà H Functionalization React...mentioning
confidence: 99%
“…However, the difficulties associated with the synthesis of stable yet catalytically active and efficient chiral gold(III) complexes hinders this approach [100–106] . Therefore, number of other strategies has been introduced to induce enantioselectivity in gold‐catalyzed transformations [107–112] . As far as C−H functionalization is concerned, following approaches have been utilized thus far: 1) use of chiral bulky ligands to create an effective chiral pocket; 2) use of a bifunctional ligand capable of establishing secondary interaction with substrates; 3) use of chiral counter‐anions; 4) use of chiral organo‐catalyst along with achiral gold complex.…”
Section: Introductionmentioning
confidence: 99%
“…This exceptional activity results from both electronic and stereo effects: on one hand, the π-acidic character of the phosphite weakens the metal-CO bond, thereby allowing a faster CO dissociation; on the other hand, the ligand’s large cone angle allows the coordination of only one phosphite to the metal centre, even when used in large excess, which results in a low global steric hindrance around the metal centre [ 17 , 18 ]. Moreover, the design and synthesis of chiral phosphite ligands also play a key role in the development of asymmetric catalysis [ 19 , 20 , 21 , 22 ]. Among them, monophosphite ligands based on the binaphthyl backbone [ 23 ] have earned a prominent status due to their synthetic availability and efficient applications in a large number of enantioselective catalytic reactions, namely in hydrogenation [ 24 , 25 , 26 , 27 , 28 ], hydrovinylation [ 29 , 30 ] and allylic substitutions [ 28 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%